Education of Ginger Drink and Accupresure as Theraphy to Relieving Primary Dismenorrhea - Nikmah Jalila Ritonga; Anuhgera, Diah Evawanna; Sitorus, Riris (JURNAL PENGMAS KESTRA (JPK), 2023)
Pain that comes with primary dysmenorrhea during menstruation often interferes with daily activities. Many dysmenorrhea sufferers do not understand how to control the pain that comes and many also use analgesic drugs in each menstrual period. Consumption of red ginger drinks and acupressure can reduce menstrual pain during primary dysmenorrhea. Provision of health education by utilizing non-pharmacological therapies, namely red ginger powder drink and acupressure for women of childbearing age can empower women to manage menstrual pain which will always be there every month. The purpose of this community service is to increase the knowledge and understanding of women of childbearing age in dealing with primary dysmenorrhea. The activity was carried out at the student dormitory of the Nutrition Study Program, Faculty of Public Health Medistra Institute of Health Lubuk Pakam. The partners in this dedication were 45 students in the first semester of the Nutrition Study Program, Faculty of Public Health, Medistra Institut of Health Lubuk Pakam. Implementation of activities begins with planning, implementation and evaluation. The educational method used is lectures and demonstrations with data collection starting from the pretest and posttest. The results of education in this activity before it was carried out the average of respondents who had good knowledge was 31.12% and after education it increased to 95.55 respondents who had good knowledge. The education implementation was going well, the respondents seemed to listen well and actively asked questions during the question and answer session. Health education is one of the activities that can increase the level of knowledge in women of childbearing age regarding the management of primary dysmenorrhea consuming red ginger drinks and doing acupressure during menstrual periods.